Microwave-assisted graphene oxide/carbon spheres with silver nanoparticles: dual catalyst for peroxide detection and antibacterial use - Thanh Long Phan; Thanh Tho Le; Van-Dat Doan; Huynh Anh Vu Truong; Van Tan Le (Royal Society Open Science)
In this study, a novel nanocomposite was rationally engineered by embedding silver nanoparticles (AgNPs) into tannic acid-derived carbon spheres (Cs), followed by their distribution on graphene oxide (GO) sheets (AgNPs@Cs-TA@GO), aiming to enhance catalytic and antibacterial performance. The fabrication process was expedited using a microwave-assisted technique. The AgNPs@Cs-TA@GO nanocomposite with the core based on AgNPs with an average diameter of 21 nm showed significant peroxidase-like activity by oxidizing 3,3′,5,5′-tetramethylbenzidine to its oxidized form in the presence of H2O2. This compassionate H2O2 colorimetric detection allowed for quick identification of H2O2 in a broad range (0.6–9.0 ppm) with a low detection limit of 0.2 ppm (S/N = 3). The viability of this method was confirmed by qualitatively detecting H2O2 residual in aquaculture water samples. Additionally, the antibacterial assays, conducted using the agar well diffusion method demonstrated pronounced inhibitory effects against Vibrio parahaemolyticus ATCC 17802 (Gram-negative) and Staphylococcus aureus ATCC 25923 (Gram-positive), with inhibition zones of 46.1 and 49.3 mm, respectively. The rapid microwave-assisted incorporation of AgNPs into Cs within the GO network not only improves synthesis duration but also the catalytic and antibacterial performances as a result of minimized coagulation and promoting electron transfer on the AgNPs’ surface.